Programs for the development of socio-emotional competencies in school education teachers: A narrative review. - Montero Chicoma, María del Pilar (2023)
The relevance that socio-emotional learning and the development of students’ socio-emotional skills currently have in school education has brought as consequences new educational scenarios that demand from teachers the transformation of their role and functions, as well as a review of their own skills and/or socio-emotional competencies. In this sense, great interest has arisen regarding the development of these competencies in teachers, through their participation in the implementation of training programs, both at the level of professional training and/or instruction during their professional practice. This study reviews 18 investigations that evaluated the effectiveness of programs aimed at developing socio-emotional skills in schoolteachers. The results revealed the impact of these programs on teachers´ socio-emotional skills and on their psychological health and performance of duties. Likewise, the theoretical and methodological characteristics of these programs were analyzed